The Development of Animation-Based Learning Videos in Comparative Material for Class VII on Junior High School - Putri, Desti Tatian; Izzati, Nur (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
This research is motivated by the need for more learning media development to support students' learning processes. This research aims to determine the validity of animation-based learning videos that will be developed in class VII Junior High School (Sekolah Menengah Pertama/SMP). In the implementation process, this research adopted the (R&D) method called Research and Development in foreign languages, referring to the 4D development model. To support the method used by researchers, a data collection tool was used as a validation questionnaire given to material expert validators, media expert validators, and language expert validators. From the validation results, information was obtained in the form of the feasibility of animation-based learning videos in comparative material for class VII SMP, which were developed in the very valid category, with a percentage of media expert assessment of 90%, material expert assessment of 91.4% and language expert assessment of 86%. Based on the overall data analysis results, the learning video media that will be developed is feasible and can be implemented in the learning process in class VII SMP.